2021
DOI: 10.1155/2021/1625915
|View full text |Cite|
|
Sign up to set email alerts
|

The Long-Term Change of Arrhythmias after Transcatheter Closure of Perimembranous Ventricular Septal Defects

Abstract: Objectives. To observe and analyze the long-term change of different types of arrhythmias after transcatheter closure of perimembranous ventricular septal defect (pmVSD). Methods. We retrospectively collected the data of patients who underwent pmVSD closure in our institution from March 2002 to December 2010. Results. One hundred thirty-nine patients met the inclusion criteria, of which 265 (25.5%) had early arrhythmia. They were classified into two categories: conduction abnormality (191/1039; 18.4%) and orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Serious arrythmia rarely occurs during follow-up. However, a higher incidence of serious postoperative arrhythmia has been reported in patients treated using an eccentric occluder (26). The proposed explanation is that the occurrence of a heart block after closure is due to conduction impairments caused by occluder compression.…”
Section: Complicationsmentioning
confidence: 99%
“…Serious arrythmia rarely occurs during follow-up. However, a higher incidence of serious postoperative arrhythmia has been reported in patients treated using an eccentric occluder (26). The proposed explanation is that the occurrence of a heart block after closure is due to conduction impairments caused by occluder compression.…”
Section: Complicationsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%